Pelvic expansion hidden by concomitant lumbar compression as a cause of sciatica - report of three cases: Ekspanzivni procesi v mali medenici, prikriti s sočasno lumbalno kompresijo, kot vzrok lumboishialgije - prikaz treh primerov - Bunc, Gorazd; Ravnik, Janez; Voršič, Matjaž (Acta Medico-Biotechnica, 2021)
Purpose: Three patients with sciatica caused by contemporary involvement of intra- and extraspinal compression of the sciatic nerve are presented.Case report: The diagnostic workup initially revealed intraspinal compression as the cause of sciatica. All patients underwent surgery that did not lead to clinical improvement. Additional diagnosis in two patients and autopsy in one revealed that residual pain was caused by nerve sheath tumors in two cases and pelvic abscess compression of the lumbosacral plexus in the third case.Conclusion: Extraspinal compression of the sciatic nerve should be considered where standard surgical decompression of the intraspinal cause of sciatica fails to improve the clinical picture.
Keywords: extraspinal nerve root compression; Intraspinal nerve root compression; lumbar radiculopathy; sciatic nerve; malignant nerve sheath tumors genetic markers